The Adversary or the Devil?: Semantic Analysis of Wiþer-Nouns in Old English - Sylwanowicz, Marta; Wojtyś, Anna (Studia Anglica Posnaniensia, 2020)
This paper discusses wiþer-nouns in Old English with the aim to verify which of them were applied with reference to ‘(the) evil spirit’. Thus, the texts compiled in the Dictionary of Old English Corpus have been searched for all the above-listed items. The identification of their uses has allowed us not only to determine the frequency of the words in question but also to specify whether the sense of ‘(the) evil spirit’ was core or peripheral for each lexeme.